2022
DOI: 10.5751/jfo-00057-930106
|View full text |Cite
|
Sign up to set email alerts
|

Foraging and roosting habitat of Eastern Whip-poor-wills in the northeastern United States

Abstract: The Eastern Whip-poor-will (Antrostomus vociferus: hereafter whip-poor-will) has been declining from historical population levels throughout its range in the northeast. Although whip-poor-wills have been reported to use a variety of habitats, most recent studies have associated whip-poor-wills with open canopy habitats, such as early-successional habitats or forest edges. However, there remain substantial gaps in our understanding of whip-poor-wills' habitat associations. For example, historical accounts state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Terrestrial birds are the type of birds that are generally found on the ground, not only foraging but also nesting and roosting on the ground. However, most terrestrial birds that do fly generally stay low above the ground or close to cover when flying (Voskamp et al 2021;Spiller et al 2022). These birds contribute to energy transmission, seed dispersal, and insect and benthos balance and are the prey of carnivores.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial birds are the type of birds that are generally found on the ground, not only foraging but also nesting and roosting on the ground. However, most terrestrial birds that do fly generally stay low above the ground or close to cover when flying (Voskamp et al 2021;Spiller et al 2022). These birds contribute to energy transmission, seed dispersal, and insect and benthos balance and are the prey of carnivores.…”
Section: Introductionmentioning
confidence: 99%